10 Tests der motorischen Kontrolle bei Patienten mit Rückenschmerzen - Vielitz, Arne (manuelletherapie, 2020)
Biele C, Möller D, von Piekartz H et al. Validity of Increasing the Number of Motor Control Tests within a Test Battery for Discrimination of Low Back Pain Conditions in People Attending a Physiotherapy Clinic: a Case-Control Study. MJ Open 2019; 25: e032340. doi:10.1136/bmjopen-2019-032340